Rheological Characteristics of Highly Concentrated Silica Glass Suspensions for 3D Printing of Refractories; Refractories and Industrial Ceramics; Vol. 64, iss. 6 - Sharafeev Sh. M. Sharif Mnirovich; Kazmina O. V. Olga Viktorovna; Gubanov A. V. Aleksandr Valerjevich; Mezhenin A. V. Aleksandr Vladimirovich; Polushin G. V. Gleb Vladimirovich; Kutugin V. A. Viktor Aleksandrovich (2024, 2024)
Title screen